A study on customer satisfaction on hotel services that focuses on front office, guest room and restaurant at Permai Park Inn International Kuala Terengganu / Rohana Robiah Ariffin - Ariffin, Rohana Robiah (Faculty of Business and Management, 1998)
The advent of deregulation and competition in the hotel industry in Malaysia has brought significant challenges to both organization and customer. It has been said that the only person in the world who appreciates a change is a wet baby. But the willingness and the ability of managers in service firms to respond to the dramatic changes affecting the service economy will determine whether their own organizations survive and prosper or go down to defeat at the hands of more agile and adaptive competitors. Competitive market demand new innovative value added services. The service sector of the economy can best be characterized by its diversity. Permai Park Inn International Kuala Terengganu proudly introduces a brilliant new standard of Executive Hotel Accommodation in Kuala Terengganu. Permai Park Inn International Kuala Terengganu, since opening in July 1994 has established a reputation for excellent value and friendly services with high standards. The main objective is to further build on those achievements by offering more patrons and guests focused services. The study will focus on measuring customer satisfaction in Front Office, Guest Room and Restaurant services by emphasizing on international hotel. A customer satisfaction survey on this services must be carried out in order to provide a better understanding of the current service performance and to give recommendations and suggestions to the management of Permai Park Inn about the service. The results show that the overall customers satisfaction on the current service of Permai Park Inn International Kuala Terengganu is at the good level. This means that the customer are satisfied with their current services. The factors that have contributed to the satisfaction are good courtesy between staffs and customers and the efficiency of the customer services entertainment. Most service businesses face active competition. The company need to find ways of creating meaningful competitive for their products and services. The management should be targeting segments that they can serve better than other competitors.